Competency approach in the formation of intercultural competence of students of the tourism technical school - Ochilova, Vazira (The Lingua Spectrum, 2025)
This article examines the importance and application of the competency approach in the process of forming the intercultural competence of students studying in tourism technical schools. In the context of globalization, intercultural competence is becoming important in the professional training of specialists working in the field of Tourism. The article focuses on the issues of understanding cultural differences when communicating with guests from different countries, knowing the norms of behavior characteristic of representatives of different cultures, developing skills to eliminate problems that arise in the process of intercultural communication. Within the framework of the study, the opinions of scientists about intercultural competence and a competency approach are studied, as well as practical recommendations for the formation of intercultural competence in students of the tourism Technical School are developed. The article proposed a model for the development of intercultural competence of students of the tourism technical school, the main components of which were analyzed.